Perceptions regarding the quality of life among beneficiaries of home and residential care services - Ghenta, Mihaela; Matei, ANiela Matei; Mladen-Macovei, Luise; Bobarnat, Elen-Silvana (Journal of Economic Development, Environment and People, 2020)
The article aims to present the results of a qualitative research conducted among elderly persons (aged 65 years and more) who receive home and residential care in Romania. The research objectives were to collect perceptions with regard to the overall appreciation of the quality of life and the way the quality of services received influence elderly’s image with regard to their own life. The scarcity of data on quality of life of dependent older persons recommended the use of qualitative methods. Data collection included ten semi-structured interviews with beneficiaries of social and healthcare services. Findings show that the quality of life is a multidimensional concept, very often related to the health status, the level of autonomy, the social contacts, and the existence of a social support network. The results have implications for public policy makers, and supplement the knowledge with regard to the quality of life in older age.